Mental Accounting dan Problematika Pola Perilaku Keuangan Working Student: Berhasil Atau Gagalkah? - Ricardo, William Nanda; Ginting, Rafles (Jurnal Pendidikan Akuntansi (JPAK), 2023)
Financial management is an important thing, especially for a student who works and studies, apart from the demands to achieve higher education, a student is also required to be able to live independently by supporting himself. This study aims to reveal how the strategy of a student who works and studies can manage finances with a mental accounting mindset. The research uses a descriptive qualitative method with phenomenological studies on students who work and study in the city of Pontianak. The research was carried out by conducting in-depth interviews with informants. Based on the results of the study, it was found that the mindset of mental accounting is an important basis for a student who works and studies to be able to carry out smart strategies in managing finances. Mental accounting is an important capital for students who work and study to be able to use money more effectively and efficiently.